PENGARUH PERSEPSI PERAWAT PELAKSANA TENTANG FUNGSI MANAJERIAL KEPALA RUANG TERHADAP PELAKSANAAN MANAJEMEN ASUHAN KEPERAWATAN DI RUANG RAWAT INAP RSJD Dr. AMINO GONDOHUTOMO SEMARANG - Warsito, Bambang Edi; Mawarni, Atik (Department of Nursing, Faculty of Medicine, Diponegoro University, 2007)
Influence of the Nurse’s Perception about Function of the Head Nurse Management toward Nursing Care Management Implementation at Inpatient Room of Dr. Amino Gondohutomo District Mentally Hospital in Semarang. The functions of management such as planning, organizing, guiding, monitoring, and controlling had not been done well by the head nurse. Nursing management is important to determine the nursing care services for client at inpatient room. Aim of this research was to analyse influence of the nurse’s perception about function of the head nurse management toward nursing care management implementation at Inpatient Room of Dr. Amino Gondohutomo District Mentally Hospital in Semarang. This was a quantitative and qualitative research with cross sectional approach. Population was nurses at inpatient room and all head nurses. Number of sample was 52 nurses taken by Proportionate stratified random sampling at 12 inpatient rooms. The questionair was used to collect data continued with cross check to the head nurses about perception of management. Result of this research showed that implementing of nursing care management is good (65,4%). Perception of a nurse about the head’s nurse management namely: (1) Good planning (53,8%), no significant association (p=0,857), and no influence (p=0,543, Exp B=0,700). (2) Good organizing (55,8%), no significant association (p=0,982), and no influence (p=0,982, Exp B=1,013). (3) Good guiding (75%), significant associated (p=0,002), and significant influence (p=0,035, Exp B=4,888). (4) Not good monitoring (51,9%), significant association (p=0,007), and significant influence (p=0,068, Exp B=3,679). (5) Not good controlling (59,6%), no significant association (p=0,873), and no influence (p=0,873, Exp B=1,100). Conclusion of the research is the nurse who perceives not good the head’s nurse guiding has a risk to be not implementing the nursing care management (p=0,035, Exp B=4,888), and the nurse who perceives not good the head’s nurse monitoring has a risk to be not implementing the nursing care management (p=0,068, Exp B=3,679).